2020
DOI: 10.3390/cancers12123541
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sensitive Droplet Digital PCR Assays for Detecting Urinary TERT Promoter Mutations as Non-Invasive Biomarkers for Detection of Urothelial Cancer

Abstract: Somatic mutations in the telomerase reverse transcriptase (TERT) promoter regions are frequent events in urothelial cancer (UC) and their detection in urine (supernatant cell-free DNA or DNA from exfoliated cells) could serve as putative non-invasive biomarkers for UC detection and monitoring. However, detecting these tumor-borne mutations in urine requires highly sensitive methods, capable of measuring low-level mutations. In this study, we developed sensitive droplet digital PCR (ddPCR) assays for detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…The most probable explanation of this finding is the higher false negativity rate of liquid biopsy testing observed when a specific mutation present in the tumor tissue is analysed in the plasma of patients with low tumor burden. Modern techniques with improved sensitivity would probably detect circulating mutations also in case of low mutant allele fraction (MAF) [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most probable explanation of this finding is the higher false negativity rate of liquid biopsy testing observed when a specific mutation present in the tumor tissue is analysed in the plasma of patients with low tumor burden. Modern techniques with improved sensitivity would probably detect circulating mutations also in case of low mutant allele fraction (MAF) [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that the detection of TERT promoter mutations in urine have high diagnostic accuracy and excellent diagnostic specificity for BC [ 40 , 41 ]. More recently, Hosen et al reported the development of test based on droplet digital PCR able to detect TERT promoter mutations in urine with an easy, inexpensive, non-invasive procedure [ 42 ]. Such an assay showed comparable performance with previously developed NGS-based test [ 40 ] but has the potential to be implemented in large-scale clinical application.…”
Section: Dna Mutationsmentioning
confidence: 99%
“…Droplet Digital PCR (ddPCR) was the analytical method of choice due to its ability to precisely quantify target DNA, even in case of low allelic frequency (34)(35)(36)(37). This approach to detecting TERT promoter mutations was previously proven to be comparable to the next-generation sequencing (NGS)-based validated system 'UroMuTERT' in terms of diagnostic accuracy (38).…”
Section: Introductionmentioning
confidence: 99%